2012
DOI: 10.1002/mabi.201200012
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Micelles for Delayed Release of Therapeutics from Drug‐Releasing Surfaces with Nanotubular Structures

Abstract: A new approach to engineer a local drug delivery system with delayed release using nanostructured surface with nanotube arrays is presented. TNT arrays electrochemically generated on a titanium surface are used as a model substrate. Polymer micelles as drug carriers encapsulated with drug are loaded at the bottom of the TNT structure and their delayed release is obtained by loading blank micelles (without drug) on the top. The delayed and time-controlled drug release is successfully demonstrated by controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…were able to delay gentamicin release for 6 days by adding a layer of blank (i.e., drug free) micelles on top of the loaded drug. 47 Further confirmation of sufficient drug loading and release will be performed in the next sections in which the anticancer activity of loaded drug-loaded implants will be assessed using cell culture studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…were able to delay gentamicin release for 6 days by adding a layer of blank (i.e., drug free) micelles on top of the loaded drug. 47 Further confirmation of sufficient drug loading and release will be performed in the next sections in which the anticancer activity of loaded drug-loaded implants will be assessed using cell culture studies.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Kumeria et al extended the in vitro release of gentamicin for 27 days by applying a PLGA coating layer over the surface of TNTs . In another study, Aw et al were able to delay gentamicin release for 6 days by adding a layer of blank (i.e., drug free) micelles on top of the loaded drug . Further confirmation of sufficient drug loading and release will be performed in the next sections in which the anticancer activity of loaded drug-loaded implants will be assessed using cell culture studies.…”
Section: Resultsmentioning
confidence: 99%
“…This porous oxide layer, tightly bonded to the bulk material, proved able to establish beneficial interactions with osteogenic cell types, in terms of adhesion and differentiation, while limiting bacterial attachment [10,11]. In vitro studies also indicated that TiO 2 nanostructures could be used as smart delivery systems in implants, thus enabling the possibility of releasing active molecules, such as antibiotics or loaded polymer micelles, directly at the site of implantation [12,13]. Nanotubes' length, diameter, and composition can be easily controlled by varying the processing parameter, and highly reproducible and homogeneous surfaces can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…57,58 To investigate the influence of pore size on the drug release profiles, studies from several groups confirmed that the drug release is considerably related to the dimensions of TNTs. [59][60][61][62] Aw et al studied the relationship between the length of the TNTs and anodization time, and their results demonstrated that length of TNTs is controlled by anodization time and that the drug release time was extended with an increase in the nanotube length based on drug loaded in TNT implants of different nanotube lengths (25-100 μm) and a fixed pore diameter of 110 nm.…”
Section: Dimensions Of Tnts and Surface Functionalizationmentioning
confidence: 99%